2013
DOI: 10.1891/0889-8391.27.3.210
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Cognitive and Behavioral Approaches for Reducing Cost Bias in Social Anxiety

Abstract: Cognitive-behavioral theories suggest that anxiety is maintained in part by estimates of the probability and cost of feared negative outcomes. Social phobia may be unique among the anxiety disorders in that it is characterized by overestimates of the cost of events that are objectively noncatastrophic (e.g., committing social mishaps). As such, treatment approaches that target cost bias may be particularly effective in reducing social phobia symptoms. This study examined the efficacy of 2 cost-specific techniq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…During such exposures, perceived social costs are targeted by having patients repeatedly commit blunders for the purpose of observing and learning that feared consequences (e.g., being ridiculed by others) do not typically occur (Hofmann & Scepkowski, 2006;Fang, Sawyer, Asnaani, & Hofmann, 2013). Despite the potential utility of this intervention, a recent experimental study showed that social mishap exposures may be less effective than cognitive restructuring for facilitating reductions in social cost biases and reducing symptoms of social anxiety (Possis et al, 2013). In fact, Possis et al (2013) reported that postintervention measures of social anxiety and social cost did not differ between the social mishap condition and a psychoeducation control condition.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…During such exposures, perceived social costs are targeted by having patients repeatedly commit blunders for the purpose of observing and learning that feared consequences (e.g., being ridiculed by others) do not typically occur (Hofmann & Scepkowski, 2006;Fang, Sawyer, Asnaani, & Hofmann, 2013). Despite the potential utility of this intervention, a recent experimental study showed that social mishap exposures may be less effective than cognitive restructuring for facilitating reductions in social cost biases and reducing symptoms of social anxiety (Possis et al, 2013). In fact, Possis et al (2013) reported that postintervention measures of social anxiety and social cost did not differ between the social mishap condition and a psychoeducation control condition.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the potential utility of this intervention, a recent experimental study showed that social mishap exposures may be less effective than cognitive restructuring for facilitating reductions in social cost biases and reducing symptoms of social anxiety (Possis et al, 2013). In fact, Possis et al (2013) reported that postintervention measures of social anxiety and social cost did not differ between the social mishap condition and a psychoeducation control condition.…”
Section: Introductionmentioning
confidence: 99%
“…Two small experiments found exposure treatments to be less or no more efficacious than an alternative treatment (Kim, 2008 ; Possis et al., 2013 ). In university students with elevated social anxiety ( n = 61), Possis et al.…”
Section: Resultsmentioning
confidence: 99%
“…In university students with elevated social anxiety ( n = 61), Possis et al. ( 2013 ) found that compared to a psychoeducation control, one session of cognitive restructuring (without exposure) was more efficacious at reducing social anxiety than one behavioural experiment (involving exposure). Further, there was no significant difference between improvisation‐assisted desensitisation (involving graded imaginal exposure) or music‐assisted progressive muscle relaxation (6 weekly sessions of 30 min) in reducing performance anxiety in young pianists ( n = 30; Kim, 2008 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation